Upaya Meningkatkan Kemampuan Perkembangan Kognitif melalui Permainan Bloks Uno untuk Anak Hiperaktif - Bariroh, Wasik Shofil; Chandra, Ratnasari Dwi Ade; Priatiningsih, Selasi (Universitas Lancang Kuning, 2025)
This research aims to enhance the cognitive development of hyperactive Children with Special Needs (CSN) through the game of Uno Blocks at TK Dewi Sartika Gumukmas. Hyperactive children often exhibit difficult-to-control behaviors, such as difficulty focusing, concentrating, and impaired social interaction. The Uno Blocks game was chosen because it requires concentration and can improve motor skills and focus attention. This study used a case study design and a qualitative methodology, gathering data through documentation, interviews, and observation. A child at TK Dewi Sartika with the initials KZ who exhibited hyperactive traits was the focus of the study. The research subject provided primary data, and pertinent literature provided secondary data. Data reduction, data presentation, and conclusion drawing are all part of the Miles and Huberman paradigm of data analysis. According to the study's findings, hyperactive CSNs can benefit from playing Uno Blocks in terms of their cognitive development. Their ability to solve problems, think logically, focus, and think creatively have all improved. Children were able to categorize blocks, construct increasingly intricate structures, and produce original designs. Additionally, the game promoted the growth of social and emotional competencies like emotional regulation and teamwork. The Uno Blocks game can therefore be a useful learning method to enhance the cognitive skills of hyperactive CSN, and it is intended that these results will be used as a guide by educators to create more successful educational initiatives.